Implementation of the KIR E-Test Program in the Technical Implementation Unit of the Motor Vehicle Testing Service of the Garut Regency Transportation Service - Ikeu Kania (GoAcademica Research & Publishing, 2021)
Implementing the KIR e-test program at the UPTD of the Garut Regency Transportation Service has been carried out since October 1, 2019. The KIR e-test program is a service innovation by changing the manual KIR test system using an IT-based system so that the KIR e-test application can simplify and shorten the service time for people who will do the KIR test. This study uses a qualitative method with descriptive analysis. The data collection techniques used include observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. From the results of the study, it was concluded that the implementation of the KIR e-test program had been implemented but encountered several obstacles, including information on changes in testing procedures from manual to electronic has not been informed to the public, so there are still people who think that the testing procedures carried out take a long time, so that vehicle owners prefer to use the services of brokers in testing the UPTD PKB Dishub Garut still lacks testers, especially testers who are certified and do not have a backup of e-KIR infrastructure. Implementing the KIR e-test is still prone to illegal levies because there are still brokers who call themselves service bureaus in collaboration with unscrupulous officers.